The Effects of Private Equity on Performance of European Companies - Epuri, Vladimir (2015)
This dissertation investigates the effects of private equity (PE) financing on performance of target companies. The analysis is based on a sample of 1,014 European buyouts between 2005 and 2014 and a control sample of non-buyouts constructed using propensity score matching methodology. The endogenous nature of PE buyout decision is taken into consideration by using instrumental variable approach. The study investigates three dimensions of firm performance – profitability, growth, and productivity – that are theorized to be positively affected by distinct changes in governance, capital structure and incentive system introduced by PE providers. In addition, PE buyouts are disaggregated into management buy-outs (MBOs) and management buy-ins (MBIs) and analyzed using subsamples of European countries with most active PE markets. After controlling for endogeneity, aggregated sample results indicate that buyouts register 3.6% lower sales growth and a 3.7% lower productivity growth compared to a matched sample of non-buyouts. Country-level analysis suggests both similarities and differences between countries and buyout types. Further, MBOs achieve slightly higher sales growth than MBIs with no evidence of differences in profitability, employment, and productivity. Country level analysis suggests some heterogeneity in performance across countries and buyout types. In particular, French MBOs showed 15.6% higher return on capital employed and higher productivity growth while Italian MBIs delivered 11.9% lower profitability and lower productivity growth compared to a control sample of companies.